Long-term monitoring of wetlands via remote sensing and gis: a case study from turkey - Bi̇lgi̇li̇oğlu, Baha; Gökdağ, Fatih; Baran, Duygu; Bakirman, Tolga; Yağmur, Nur; Dervişoğlu, Adalet; Gümüşay, Mustafa Ümit; Tanık, Ayşegül; Musaoğlu, Nebi̇ye (The International Institute of Knowledge Management-TIIKM, 2018)
Remote sensing that is a low cost data source capable of making temporal observations has more advantages than the traditional methods to obtain land-use/cover change maps. In this study, temporal land-use/cover change of surface water bodies in Konya Closed Basin was evaluated via Landsat satellite images for the past 30 years. The basin, located in Central Anatolia Region of Turkey, faces water scarcity problems; however, wet agricultural activities are still favoured and practiced. Therefore, water resources are becoming more important than ever; public complains about long-lasting drought conditions and on lessening of surface water resources. There are 16 surface water bodies, and 3 of them are lakes; whereas the rest are wetlands of importance. Two of them are Ramsar sites. Results indicate that the surface area of the water bodies in Konya Closed Basin declined by approximately 23.5% within the inspection years. One of the important wetlands of the basin named as Akgol Wetland has almost lost its water surface by 96% at the same time interval, and is in danger of extinction. Thus, this vulnerable wetland has been focused on in the study. The decrease of water surface in the wetland is matched with the meteorological conditions.